Estimation of Shelf Life on Pollard and Bran with Arrhenius Model on Storage at Different Temperatures - Rizqa Adisti AZ; Indah Wijayanti; Yuli Retnaini (Jurnal Ternak : Jurnal Ilmiah Fakultas Peternakan Universitas Islam Lamongan, 2021)
Fluctuating climatic and transportation conditions in Indonesia cause problems in the storage of feed ingredients. Estimating the shelf life of feed ingredients is very important to know in order to help the feed industry in the storage, availability and maintenance of the quality of the feed produced. The purpose of this study was to determine the shelf life of pollard and wheat bran at different storage temperatures based on the value of the peroxide number using the Arrhenius model. In determining shelf life, pollard and wheat bran were stored at 15, 35, and 45Â°C for 49 days. The parameter used in this research is the peroxide number. The results of this study were based on the calculation of the Arrhenius model in pollard based on the number of peroxides at a temperature of 15, 35 and 45 Â°C, the shelf life of which was 27.3 months, 22.2 months and 13.1 months, respectively. The shelf life of wheat bran is 25.1 months, 15.1 months and 14.8 months. The conclusion is that the temperature and storage time are directly proportional to the peroxide number. Meanwhile, temperature and storage time are inversely proportional to shelf life.